2012
DOI: 10.1167/iovs.12-9875
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Nerve Fiber Layer Thickness Changes in Patients with Age-Related Macular Degeneration Treated with Intravitreal Ranibizumab

Abstract: Intravitreal ranibizumab injections used to treat AMD caused a significant change in RNFL thickness after 12 months of follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
85
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 19 publications
2
85
2
Order By: Relevance
“…A similar result was also reported by ElAshry et al The authors looked at the RNLF thickness in neovascular AMD patients receiving ranibizumab injections and demonstrated no harmful effect of intravitreal ranibizumab on RNLF thickness in the short term [17]. Conversely, Martinez-de-la-Casa et al found a significant RNLF thinning after 12 months of follow-up [18]. Another issue is how the function of the ganglion cells are being affected by that thinning.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…A similar result was also reported by ElAshry et al The authors looked at the RNLF thickness in neovascular AMD patients receiving ranibizumab injections and demonstrated no harmful effect of intravitreal ranibizumab on RNLF thickness in the short term [17]. Conversely, Martinez-de-la-Casa et al found a significant RNLF thinning after 12 months of follow-up [18]. Another issue is how the function of the ganglion cells are being affected by that thinning.…”
Section: Discussionsupporting
confidence: 73%
“…We attribute this finding to the short follow-up time in that study. Someone may also think that intraocular pressure (IOP) fluctuations secondary to intravitreal injections might result in that GCC reduction, however it was shown in several studies that IOP spikes are limited to within the first few minutes of the injection procedure [18,21]. Surely, such peaks may have even induced GCC thinning, in time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structural effect of repeated IVIs on the peripapillary retinal nerve fiber layer (RNFL) is controversial and less well understood [13][14][15][16][17] . Repeated IOP elevations after IVI could lead to glaucomatous damage in the peripapillary RNFL.…”
Section: Introductionmentioning
confidence: 99%
“…Repeated IOP elevations after IVI could lead to glaucomatous damage in the peripapillary RNFL. In 2012, Martinez-de-la-Casa et al [14] described in a prospective study a significant decrease of RNFL thickness after 12 months of IVI treatment for nAMD. Very recently, Beck et al [18] found a significant decrease of the retinal ganglion cell layer in patients with nAMD compared to the fellow (untreated) eye during the course of long-term anti-VEGF therapy.…”
Section: Introductionmentioning
confidence: 99%